Pengaruh Sistem Modernisasi, Pengetahuan Pajak Dan Kondisi Keuangan Terhadap Kepatuhan Pajak UMKM - Anna Ramah Lumban Gaol; Rizka Mukhlisiah (IJAcc, 2024)
Taxes have an important role in the economy because they are the largest contributor to the state budget. One source of tax that contributes significantly to tax realisation is tax on the micro, small and medium enterprise (UMKM) sector. Significant regional economic growth provides an impetus for the development of micro, small and medium enterprises. The purpose of this study is to determine UMKM tax compliance and further improve its fulfilment of its tax obligations. The research method used in this research is a quantitative approach. The sampling technique in this study used a questionnaire consisting of 100 UMKM in Tangerang city that are still operating today. Data collection was carried out by distributing manual questionnaires by visiting one by one UMKM in Tangerang city. The data analysis technique used is descriptive analysis and multiple regression analysis using SPSS 29 software. Based on the results of the hypothesis, it can be concluded that the Modernisation System, tax knowledge, financial conditions have an effect on Tax Compliance in Tangerang City UMKM players.